SLA UNDER CONSIDERATION: AN EXPERIENCE OF A SUCCESSFUL LEARNER OF THE ENGLISH LANGUAGE (Revista Desempenho, 2018)
A second language learning experience is always discernible by its uniqueness. Each learning individual lives the singularity of this process in their own approach.   The present research performs a careful analysis of the aspects that helped composing the successful English acquisition of a sole individual. This case study investigates which of the existent theories or hypotheses in the SLA field of inquiry are related to the facts narrated by the participant, and what elements most influenced this process. A study of this nature may demonstrate how profitable it can be for current studies in SLA to deeper explore single cases as the one herewith.